Novel Predictive Scoring System for Intravenous Immunoglobulin Resistance Helps Timely Intervention in Kawasaki Disease: The Chinese Experience - Yan Wang; Shuoyin Huang; Panpan Wang; Yan Wu; Yingying Liu; Yuting Pan; Jinyuan Dong; Zhidan Fan; Haiguo Yu (Journal of Immunology Research)
Background. Approximately 10%–20% of patients with Kawasaki disease (KD) are nonresponsive to intravenous immunoglobulin (IVIG) treatment, placing them at higher risk of developing coronary heart lesions. Early detection of nonresponsiveness is crucial to curtail this risk; however, the applicability of existing predictive scoring systems is limited to the Japanese population. Our study aimed to identify a predictive scoring system for IVIG resistance in KD specific to the Chinese population. We aimed to assess the utility of three commonly used risk-scoring systems in predicting IVIG resistance and compare them to the newly developed predictive scoring system. Methods. A total of 895 patients with KD were enrolled in this retrospective review and divided into two groups: IVIG responders and nonresponders. Clinical and laboratory variables were compared between the two groups. Multivariable logistic regression models were used to construct a new scoring system. The utility of the existing and new scoring systems was assessed and compared using the area under the receiver operating characteristic curve. Results. Albumin levels, percentage of neutrophils, and hemoglobin were independent predictors of resistance by logistic regression analysis. The new predictive scoring system was derived with improved sensitivity (60.5%) and specificity (87.8%). The area under the receiver operating characteristic curve was 0.818. Conclusion. This study developed a novel risk-scoring system for predicting resistance to IVIG treatment in KD specific to the Chinese population. Although this new model requires further validation, it may be useful for improving prognostic outcomes and reducing the risk of complications associated with KD.